2021
DOI: 10.3171/2019.11.jns192374
|View full text |Cite
|
Sign up to set email alerts
|

External jugular venous sampling for Cushing’s disease in a patient with hypoplastic inferior petrosal sinuses

Abstract: The authors report the case of a 30-year-old female patient with suspected Cushing’s disease with an anatomical variation of hypoplastic inferior petrosal sinuses and nearly exclusive anterior drainage from the cavernous sinus, who underwent external jugular venous blood sampling with successful disease confirmation and microadenoma localization. The patient presented with signs and symptoms consistent with Cushing’s syndrome, but with discordant preliminary diagnostic testing. She underwent attempted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…If both sides are type 4, IPSS is virtually impossible to perform. Interestingly, Peterson et al recently reported that sampling from both external jugular veins could substitute for IPSS in rare cases [15]. Our group previously reported that, with negative MRI, postoperative remission was achieved in very rarely of their patients with negative IPSS and 50% of those with positive IPSS [11,16].…”
Section: Discussionmentioning
confidence: 82%
“…If both sides are type 4, IPSS is virtually impossible to perform. Interestingly, Peterson et al recently reported that sampling from both external jugular veins could substitute for IPSS in rare cases [15]. Our group previously reported that, with negative MRI, postoperative remission was achieved in very rarely of their patients with negative IPSS and 50% of those with positive IPSS [11,16].…”
Section: Discussionmentioning
confidence: 82%
“…BIPSS is considered the gold standard for differentiating between pituitary and ectopic sources of ACTH hypersecretion, but it cannot be used for diagnosing the location [20,21] . We believe this may be in uenced by factors such as the intercavernous sinus drainage pattern and the signi cant variation in intraoperative catheter placement.…”
Section: Discussionmentioning
confidence: 99%
“…Venous drainage of the cavernous sinus can be altered by the presence of a plexiform IPS, hypoplastic IPS, or significant anterior drainage of the cavernous sinus through the pterygoid plexus. 15 , 17 Although it has been known that cavernous sinus drainage patterns can affect or confound the results of IPS or cavernous sinus sampling, the algorithm we use here to identify drainage patterns to determine optimal sampling locations has not been described previously. 18 The identification of the site of primary drainage allows targeted microcatheter positioning to increase the probability of sampling with the highest possible fidelity, thus allowing more accurate lateralization.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Other authors have reported success with the concept of identifying the dominant drainage pattern in a single patient, leading to successful lateralization based on external jugular vein sampling. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation